Outline of the Consumer Dispute Resolution Agency as a Means of Legal Protection: Is it Optimal? - Lasatu, Asri; Jubair, Jubair; Insarullah, Insarullah; Mardin, Nurhayati; Korompot, Ratu Ratna (Jambura Law Review, 2022)
Consumer protection is an effort to guarantee legal certainty to protect consumer rights. Consumer protection is a government responsibility delegated to the Consumer Dispute Settlement Body. This responsibility is carried out through preventive and repressive efforts. The problem in this research is what is the role of Consumer Dispute Settlement Body in implementing consumer law protection in Central Sulawesi Province. Type of normative-empirical research with a mixed method approach. The analysis was carried out qualitatively-quantitatively, and the results are descriptive-analytic. The research results show that Consumer Dispute Settlement Body's role in consumer legal protection is not maximized because it is influenced by structural, substance, and societal, cultural factors.